The effect of nectar production to the gathering behaviour of honeybees and to the foraging activity of wild bees at apple flowers - P. Benedek (International Journal of Horticultural Science, 2006)
Intensity of bee visitation (honeybees and wild bees), foraging behaviour of honeybees and nectar parameters (nectar production, sugar concentration, sugar content in nectars) were inspected at 18 apple cultivars for three consecutive years. Honeybee visitation was calculated to be some 3.07 bee visits at a single apple flower a day but wild bee activity was very low, only some 0.11 wild bee visits per flower per day.